Circulating Phylloquinone Concentrations and Risk of Type 2 Diabetes: A Mendelian Randomization Study - Zwakenberg, Sabine R.; Remmelzwaal, Sharon; Beulens, Joline W.J.; Booth, Sarah L.; Burgess, Stephen; Dashti, Hassan S.; Imamura, Fumiaki; Feskens, Edith J.M.; van der Schouw, Yvonne T.; Sluijs, Ivonne (Diabetes (New York, N.Y.), 2019)
This study investigated the causal relation between circulating phylloquinone (vitamin K1) concentrations and type 2 diabetes by using a Mendelian randomization (MR) approach. We used data from three studies: the European Prospective Investigation into Cancer and Nutrition (EPIC)-InterAct case-cohort study, Diabetes Genetics Replication and Meta-analysis (DIAGRAM), and the UK Biobank, resulting in 69,647 subjects with type 2 diabetes. We calculated a weighted genetic risk score including four genetic variants previously found to be associated with circulating phylloquinone concentrations. Inverse-variance weighted analysis was used to obtain a risk ratio (RR) for the causal relation between circulating phylloquinone concentrations and risk of type 2 diabetes. Presence of pleiotropy and the robustness of the results were assessed using MR-Egger and weighted-median analyses. Genetically predicted concentrations of circulating phylloquinone were associated with lower risk of type 2 diabetes with an RR of 0.93 (95% CI 0.89; 0.97) per every natural logarithm (Ln)-nmol/L–unit increase in circulating phylloquinone. The MR-Egger and weighted median analyses showed RRs of 0.94 (0.86; 1.02) and 0.93 (0.88; 0.98), respectively, indicating no pleiotropy. In conclusion, our study supports that higher circulating phylloquinone may be causally related with lower risk of type 2 diabetes, highlighting the importance of sufficient phylloquinone in the human diet.